Effect of Supplemental DL-Methionine to Low Protein Diet on Production Performance, Egg Quality and Serum Biochemical Indices of Vanaraja Laying Hens : - Panda, Arun Kumar; B. Sahoo; Anil Kumar (Indian Journal of Animal Nutrition, 2023)
The present study was conducted to evaluate the effect Supplemental DL-Methionine to low protein diet on production performance, egg quality and serum biochemical indices of Vanaraja laying hens. Ninety six, Vanaraja laying hens (28 wks) were randomly distributed into four dietary treatment groups with three replicates of 8 birds in each pen. A standard diet containing 2600kcal/kg ME, 15% CP, 0.7% lysine and 0.28% methionine was formulated which served as control. Subsequently, three experimental diets were formulated to contain 0.32, 0.36 and 0.40% DLM in the diets. A measured quantity of each diet was fed to one of the treatment groups for a period of 8 weeks to study their performance. Dietary supplementation of DL methionine had no influence on body weight gain, egg production and feed efficiency of Vanaraja laying hens. However, egg weight and egg mass output increased significantly due to supplemental DLM at 0.04% (0.32% DLM diet) with no further improvements thereafter. None of the egg quality parameters (albumen, yolk and eggshell%; albumen index, yolk index, shape index and eggshell thickness) except the Haugh unit was influenced due to the levels of supplemental DLM in the diet of Vanaraja laying hens. Increasing the levels of DLM to 0.32% in the diet significantly improved the Haugh unit compared to the control group. Dietary supplementation of DLM at 0.04% significantly increased the serum protein and calcium concentration of laying hens. From the finding of the present study it is concluded that 0.04% supplemental DLM to the diet containing 2600kcal/kg ME, 15% CP, 0.7% lysine and 0.28% methionine is adequate in eliciting optimum performance in Vanaraja laying hens.